Pendidikandan Politik diIndonesia - Nanik Kristanto (Sekolah Tinggi Teologi Duta Panisal, 2020)
Education and politics are two inseparable notions. If you look at the world of field these two things are interrelated with one another. politics as a control tool in the government system, while education is one of the important pillars in the government system so that education will be affected by the political system of government. Politics will also be affected by the education system in the long run. Education in Indonesia can never be separated from politics. Politics is very easily influenced and determined by political elites and political parisapsi that produce political ethics. Political elites are actors who rule and make wisdom when in power. Elite and power are never separated from each other. Education in Indonesia was never separated from the ruling political elites at the time. With education in Indonesia, educated people will not be easy to be influenced and contaminated by political slogans using religion as false labels. Let the government continue to strive to advance education and educate the nation's life. So that Indonesia remains a country of nationalism.